Porous layered nickel-rich oxide positive electrode material and preparation method and application thereof
By introducing gradient-distributed pores into the nickel-rich layered oxide positive electrode material, the stress changes inside the buffer material are solved, and the microcracks and separation problems caused by the increase in stress during the circulation process are achieved, achieving higher cyclic stability and capacity.
Patent Information
- Application Number
- CN202411877271.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
AI Technical Summary
The anisotropic shrinkage and expansion caused by the H2H3 phase change during the circulation process of nickel-rich layered oxide positive electrode material leads to an increase in the internal stress of the material, resulting in microcracks and separation, which accelerates the side reaction between the electrolyte and the cracks, resulting in material failure.
The preparation method of porous layered nickel-rich oxide positive electrode material is adopted. By mixing and dissolving nickel salt, manganese salt and cobalt salt, adding template agent and pore-forming agent, and after heating reaction, cooling, washing and high-temperature calcination, a porous layered structure with gradient distribution pores is formed, and the stress changes inside the buffer material are buffered.
Through the gradient porous strategy, the internal stress of the material is reduced, the formation of cracks is suppressed, the cyclic stability and capacity of the material are improved, and the impedance growth is limited.
Smart Images

Figure CN119683701A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium metal batteries, and in particular relates to a porous layered nickel-rich oxide positive electrode material and a preparation method and application thereof. Background Art
[0002] The rapid development of new energy vehicles in recent years has put forward higher requirements on the energy density, cycle life and power density of lithium secondary batteries, and the positive electrode material is the key to the performance breakthrough of lithium secondary batteries. x Co y Mn 1-x-y O2, x ≥ 0.8, NCM) has been widely used in the lithium battery field due to its high specific energy and relatively low cost compared with cobalt-rich positive electrodes.
[0003] However, the practical application of nickel-rich NCM is still plagued by complex chemical mechanical degradation, including surface lattice collapse, oxygen release, cathode electrolyte side reactions and transition metal dissolution, which greatly affect the cycle life and safety of the battery. 3+ , forming binary or ternary layered oxides, improving the structural stability and cycle performance of the material, among which the ratio of Co and Mn is flexibly adjusted, the material composition and electrochemical properties are balanced, and a nickel-rich NCM or NCA ternary positive electrode material with higher energy density is constructed. However, during the cycle of the nickel-rich ternary positive electrode material, the anisotropic contraction and expansion of the primary particles caused by the H2H3 phase transition will aggravate the stress inside the material, induce the generation and expansion of microcracks inside the material, and then lead to the separation and pulverization of the primary particles, accelerate the side reaction between the electrolyte and the microcracks, and finally lead to material failure.
[0004] Therefore, it is urgent to develop a porous layered nickel-rich oxide cathode material to introduce gradient-distributed pores into polycrystalline NCM secondary particles, aiming to improve the cycle stability of the cathode material. Summary of the invention
[0005] Based on the defects of the prior art, the first purpose of the present invention is to provide a method for preparing a porous layered nickel-rich oxide positive electrode material; the second purpose of the present invention is to provide a porous layered nickel-rich oxide positive electrode material; the third purpose of the present invention is to provide an application of a porous layered nickel-rich oxide positive electrode material in the preparation of a lithium-ion battery.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] In one aspect, the present invention provides a method for preparing a porous layered nickel-rich oxide positive electrode material, comprising the following steps:
[0008] Step 1, mixing nickel salt, manganese salt and cobalt salt and dissolving them in water to form solution A;
[0009] Step 2, adding the template to solution A and stirring evenly to obtain solution B;
[0010] Step 3, heating solution B for reaction, washing and drying the precipitated product after cooling to obtain precursor C;
[0011] Step 4, the precursor C, lithium salt and pore-forming agent are mixed evenly, calcined at high temperature in an inert gas atmosphere, and cooled to obtain product D;
[0012] Step 5: The product D is washed to remove the pore-forming agent and dried, and heat-treated in an oxygen atmosphere to obtain a final porous layered nickel-rich oxide positive electrode material.
[0013] The present invention develops a simple molten salt-assisted synthesis route to introduce gradient-distributed pores into polycrystalline NCM secondary particles. The gradient-porous strategy creates void spaces to buffer the anisotropic volume changes of primary particles, effectively mitigating intergranular fracture and limiting impedance growth. It not only increases the capacity of NCM cathodes, but also greatly improves their cycling stability.
[0014] In the above preparation method, preferably, the nickel salt is selected from a combination of one or more of nickel acetate, nickel sulfate, nickel nitrate, nickel chloride and nickel oxalate; but not limited thereto.
[0015] In the above preparation method, preferably, the manganese salt is selected from a combination of one or more of manganese acetate, manganese sulfate, manganese nitrate, manganese chloride and manganese oxalate; but not limited thereto.
[0016] In the above preparation method, preferably, the cobalt salt is selected from one or more combinations of cobalt sulfate, cobalt nitrate, cobalt chloride and cobalt oxalate; but not limited thereto.
[0017] In the above preparation method, preferably, in step 1, the molar ratio of the nickel salt, the manganese salt and the cobalt salt is (8-8.5):(1-1.3):(0.5-1), and the total molar ratio is 10.
[0018] In the above preparation method, preferably, in step 2, the template is selected from a combination of one or more of urea, manganese dioxide and calcium carbonate; but not limited thereto.
[0019] In the above preparation method, preferably, the molar ratio of the template to the nickel salt is (1-2):1.
[0020] In the above preparation method, preferably, in step 3, the temperature of heating the solution B for reaction is 130-270° C., and the reaction time is 12-24 h.
[0021] In the above preparation method, preferably, the precipitated product after cooling is washed with deionized water for 1 to 3 times.
[0022] In the above preparation method, preferably, the drying is carried out by vacuum drying, the drying temperature is 70 to 90° C., and the drying time is 15 to 20 hours.
[0023] In the above preparation method, preferably, in step 4, the lithium salt is selected from lithium carbonate and / or lithium hydroxide; but not limited thereto.
[0024] In the above preparation method, preferably, the pore-forming agent is selected from potassium sulfate and / or potassium carbonate; but not limited thereto.
[0025] In the above preparation method, preferably, the molar ratio of the precursor C, the lithium salt and the pore-forming agent is 1:(1.02-1.08):(0.07-0.13), and the total molar ratio of the lithium salt and the pore-forming agent is 1.15.
[0026] In the above preparation method, preferably, in step 4, the inert gas is selected from a combination of one or more of argon, helium and nitrogen; but not limited thereto.
[0027] In the above preparation method, preferably, the heating rate of the high-temperature calcination is 5 to 15°C / min; the insulation temperature is 700 to 800°C; and the insulation time is 10 to 20h.
[0028] In the above preparation method, preferably, in step 5, the product D is washed at least once with deionized water and ethanol in sequence.
[0029] In the above preparation method, preferably, the temperature of the heat treatment in an oxygen atmosphere is 600-800° C., and the time of the heat treatment is 6-12 hours.
[0030] On the other hand, the present invention also provides a porous layered nickel-rich oxide positive electrode material, which is prepared by the above-mentioned preparation method.
[0031] In another aspect, the present invention also provides the use of the above-mentioned porous layered nickel-rich oxide positive electrode material in the preparation of lithium-ion batteries.
[0032] Beneficial effects of the present invention:
[0033] (1) The preparation method of the porous layered nickel-rich oxide positive electrode material of the present invention is simple. A distributed interconnected internal pore gradient is created in the NCM secondary particles through a simple molten salt-assisted method, which effectively reduces the internal strain accumulation. The inner core porosity is higher than the outer core porosity, which can effectively inhibit the formation of cracks, and the design of the gradient voids can provide sufficient space to slowly offset the anisotropic volume changes of the primary particles.
[0034] (2) In the preparation method of the porous layered nickel-rich oxide positive electrode material of the present invention, a small amount of pore former is added, and the pore former and the lithium source are heated to form a molten salt mixture, which can be injected into the secondary particles of the NCM precursor. The lithium source phase is consumed by the NCM precursor to be converted into the NCM product, and the pore former phase remains between the primary particles. The pore-forming component can regulate the growth of the primary particles, thereby realizing the microstructural regulation of the secondary ions of the polycrystalline NCM. The potassium element in the pore former component can provide a columnar effect, thereby improving the structural stability of the NCM; and the pore former has been removed by washing with water.
[0035] (3) The porous layered nickel-rich oxide positive electrode material prepared by the present invention has a highly ordered layered structure, minimal Li-Ni cation mixing, higher capacity and excellent cycle stability.
[0036] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 This is a scanning electron microscope image of the porous layered nickel-rich oxide positive electrode material NCM prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0039] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The process, conditions, reagents, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art, and the present invention does not particularly limit the contents.
[0040] Embodiment 1:
[0041] This embodiment provides a porous layered nickel-rich oxide positive electrode material and a preparation method thereof. The specific preparation method is as follows:
[0042] (1) Nickel acetate, manganese acetate and cobalt acetate were added into deionized water in a molar ratio of 8:1:1, and stirred to form a clear solution A.
[0043] (2) Urea (NH2CONH2) was added to the above solution A, stirred at room temperature for 2.5 hours, and mixed to obtain solution B, wherein the molar mass of urea was 1.5 times that of nickel acetate.
[0044] (3) Solution B was transferred to a reactor, sealed in an oven and heated to 220°C for 15 h. After the reaction, the solution was cooled at room temperature, washed twice with deionized water, and vacuum dried at 80°C for 16 h to obtain precursor C.
[0045] (4) Precursor C, lithium hydroxide and potassium carbonate were mixed uniformly in a molar ratio of 1:1.05:0.1, heated to 700°C in high-purity argon at a heating rate of 10°C / min, calcined and kept at this temperature for 15 h, and then cooled to room temperature to obtain the target reaction product D.
[0046] (5) The reaction product D was washed once with cold deionized water and once with ethanol, and after removing the pore-forming agent, it was dried at 75°C for 7 h; and was heat-treated again at 700°C under flowing oxygen for 8 h to obtain a porous layered nickel-rich oxide positive electrode material NCM, denoted as: LiNi 0.8 Co 0.1 Mn 0.1 O2. Its scanning electron microscope image is as follows Figure 1 shown.
[0047] Embodiment 2:
[0048] This embodiment provides a porous layered nickel-rich oxide positive electrode material and a preparation method thereof. The specific preparation method is as follows:
[0049] (1) Nickel acetate, manganese acetate and cobalt acetate were added into deionized water in a molar ratio of 8.3:1.1:0.6, and stirred to form a clear solution A.
[0050] (2) Urea (NH2CONH2) was added to the above solution A, stirred at room temperature for 2.5 hours, and mixed to obtain solution B, wherein the molar mass of urea was 1.2 times that of nickel acetate.
[0051] (3) Solution B was transferred to a reactor, sealed in an oven and heated to 220°C for 15 h. After the reaction, the solution was cooled at room temperature, washed twice with deionized water, and vacuum dried at 80°C for 16 h to obtain precursor C.
[0052] (4) Precursor C, lithium hydroxide and potassium carbonate were mixed uniformly in a molar ratio of 1:1.07:0.08, heated to 750°C in high-purity argon at a heating rate of 10°C / min, calcined and kept at this temperature for 12 h, and then cooled to room temperature to obtain the target reaction product D.
[0053] (5) The reaction product D was washed once with cold deionized water and once with ethanol, and after removing the pore-forming agent, it was dried at 75°C for 7 h; and was heat-treated again at 700°C under flowing oxygen for 8 h to obtain a porous layered nickel-rich oxide positive electrode material NCM, denoted as: LiNi 0.83 Co 0.11 Mn 0.06 O2.
[0054] Embodiment 3:
[0055] The buckling performance test experiment was carried out on the porous layered nickel-rich oxide positive electrode material NCM prepared in Examples 1 and 2 of the present invention and the commercially available NCM positive electrode material.
[0056] Preparation of the button:
[0057] The porous layered nickel-rich oxide positive electrode material prepared in Examples 1 and 2 and two commercially available NCM811s from different manufacturers were respectively mixed with acetylene black and polytetrafluoroethylene binder in a mass ratio of 90:5:5, ground and mixed with N-methylpyrrolidone as solvent, then coated on aluminum foil, and placed in a forced air drying oven at 80°C for 3 hours, and then dried in a vacuum drying oven at 120°C for 12 hours.
[0058] The dried electrode was rolled with a roller machine, and the aluminum foil was cut with a slicer into circular electrode pieces with a diameter of 1.3 cm. The loading amount of active material was controlled at 8 ± 0.1 mg / cm 2 About; half-cells were assembled in an argon atmosphere glove box, with a water partial pressure of ≤0.1ppm and an oxygen partial pressure of ≤0.1ppm; metallic lithium was used as the counter electrode, 1M LiPF6 (EC / DMC, volume ratio of 1:1:1) solution was used as the electrolyte, and Celgard 16μm was used as the separator to assemble a CR2032 button cell, which was charged and discharged at room temperature using a constant current charge and discharge mode, with a voltage range of 2.8 to 4.3V, first cycled 3 times at 0.1C, and then cycled 100 times at 0.3C (1C = 230mAg -1 ), the experimental results are shown in Table 1 below.
[0059] Table 1:
[0060]
[0061] It can be seen from the experimental data in Table 1 above that the porous layered nickel-rich oxide NCM positive electrode materials of Examples 1 and 2 of the present invention have higher capacity and excellent cycle stability in lithium secondary battery tests compared with the two commercially available NCM positive electrode materials.
[0062] Embodiment 4:
[0063] The porous layered nickel-rich oxide positive electrode material NCM prepared in Examples 1 and 2 of the present invention and the commercially available NCM positive electrode material were subjected to an X-ray diffractometer test experiment. Specifically:
[0064] The crystal structures of Examples 1 and 2 and Comparative Groups 1 and 2 were analyzed by powder XRD using an X-ray diffractometer (Bruker D8 ADVANCE Da Vinci, Cu Kα radiation). The experimental results are shown in Table 2 below.
[0065] Table 2:
[0066]
[0067]
[0068] It can be seen from the experimental results in Table 2 above that the porous layered nickel-rich oxide NCM positive electrode materials of Examples 1 and 2 of the present invention have a highly ordered layered structure and minimal Li-Ni cation mixing compared to the two commercially available NCM positive electrode materials.
[0069] The present invention uses specific embodiments to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for preparing a porous layered nickel-rich oxide positive electrode material, characterized in that: The steps include: Step 1, mixing nickel salt, manganese salt and cobalt salt and dissolving them in water to form solution A; Step 2, adding the template to solution A and stirring evenly to obtain solution B; Step 3, heating solution B for reaction, washing and drying the precipitated product after cooling to obtain precursor C; Step 4, the precursor C, lithium salt and pore-forming agent are mixed evenly, calcined at high temperature in an inert gas atmosphere, and cooled to obtain product D; Step 5: The product D is washed to remove the pore-forming agent and dried, and heat-treated in an oxygen atmosphere to obtain a final porous layered nickel-rich oxide positive electrode material.
2. The preparation method according to claim 1, characterized in that: The nickel salt is selected from a combination of one or more of nickel acetate, nickel sulfate, nickel nitrate, nickel chloride and nickel oxalate; Preferably, the manganese salt is selected from a combination of one or more of manganese acetate, manganese sulfate, manganese nitrate, manganese chloride and manganese oxalate; Preferably, the cobalt salt is selected from one or more combinations of cobalt sulfate, cobalt nitrate, cobalt chloride and cobalt oxalate.
3. The preparation method according to claim 1 or 2, characterized in that: In step 1, the molar ratio of the nickel salt, the manganese salt and the cobalt salt is (8-8.5):(1-1.3):(0.5-1), and the total molar ratio is 10.
4. The preparation method according to claim 1, characterized in that: In step 2, the template is selected from a combination of one or more of urea, manganese dioxide and calcium carbonate; Preferably, the molar ratio of the template to the nickel salt is (1-2):
1.
5. The preparation method according to claim 1, characterized in that: In step 3, the solution B is heated to react at a temperature of 130 to 270° C. for a reaction time of 12 to 24 hours; Preferably, the cooled precipitated product is washed 1 to 3 times with deionized water; Preferably, the drying is performed by vacuum drying, the drying temperature is 70 to 90° C., and the drying time is 15 to 20 hours.
6. The preparation method according to claim 1, characterized in that: In step 4, the lithium salt is selected from lithium carbonate and / or lithium hydroxide; Preferably, the pore-forming agent is selected from potassium sulfate and / or potassium carbonate; Preferably, the molar ratio of the precursor C, the lithium salt and the pore-forming agent is 1:(1.02-1.08):(0.07-0.13), and the total molar ratio of the lithium salt and the pore-forming agent is 1.
15.
7. The preparation method according to claim 1 or 6, characterized in that: In step 4, the inert gas is selected from a combination of one or more of argon, helium and nitrogen; Preferably, the heating rate of the high-temperature calcination is 5 to 15°C / min; the insulation temperature is 700 to 800°C; and the insulation time is 10 to 20 hours.
8. The preparation method according to claim 1, characterized in that: In step 5, the product D is washed at least once with deionized water and ethanol in sequence; Preferably, the temperature of the heat treatment in an oxygen atmosphere is 600-800° C., and the time of the heat treatment is 6-12 hours.
9. A porous layered nickel-rich oxide positive electrode material, prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the porous layered nickel-rich oxide positive electrode material according to claim 9 or the porous layered nickel-rich oxide positive electrode material prepared by the preparation method according to any one of claims 1 to 8 in preparing lithium-ion batteries.
Citation Information
Patent Citations
Nickel-rich layered oxide used as positive electrode material of lithium ion battery, and preparation method for nickel-rich layered oxide
CN106532036A
Porous nickel cobalt lithium manganate ternary positive electrode material and preparation method thereof
CN113213556A
Positive electrode material, preparation method thereof and lithium ion battery
CN117727910A